Safety Measures In Neuro-Surgical Theatre: An Institutional Protocal - Dhimal, Kaushila; Limbu, Punam; Biswakarma, Pushpa (Eastern Green Neurosurgery, 2019)
Effective teamwork in the operating theatre is of vital importance for same and smooth surgery. The main goal of safety measures is to reduce mortality, morbidity, improves communication and team work ,reduce operation time, ensuring the patient is secure in operation table, and also to ensure the operating staff and surgeons from advertent injuries.